Digital Marketing Technology Transformation as Instrument for Enhancing Community Creative Economy through Owabong Tourism Attraction - Rohmah Nia Chandra Sari (Community Development and Empowerment, 2026)
The tourism sector serves as a primary driver for the creative economy, with effective marketing communication being the key to its sustainability. This study aims to analyze the implementation of the Integrated Marketing Communication (IMC) strategy at Owabong Tourism, Purbalingga, in enhancing tourist attraction and its impact on the community's creative economy. Utilizing a descriptive qualitative research method, data were gathered through in-depth interviews with the marketing division, field observations, and documentation studies. The findings indicate that Owabong has undergone a strategic transformation from conventional media to an integrated digital ecosystem. Analysis based on Kotler’s eight IMC elements reveals that interactive marketing via social media (Instagram and TikTok) and segmented sales promotions are the most dominant instruments in attracting visitors. While digital marketing has successfully expanded market reach, challenges such as audience digital literacy and reliance on paid advertising remain significant hurdles. This study concludes that the synergy between digital marketing technology and adaptive regional enterprise governance not only significantly boosts tourist visits reaching 150,000 during peak periods but also creates a multiplier effect for local creative economy actors.